The Problem of the Pannus: Physician Preference Survey and a Review of the Literature on Cesarean Skin Incision in Morbidly Obese Women - Smid, Marcela C.; Smiley, Sarah G.; Schulkin, Jay; Stamilio, David M.; Edwards, Rodney K.; Stuebe, Alison M. (American Journal of Perinatology, 2016)
Objective This study aims to determine preferences of a nationally representative sample of obstetrician/gynecologists (OB/GYNs) regarding cesarean delivery (CD) incision practices for women with morbid obesity (body mass index ≥ 40 kg/m2).Study Design We conducted an online survey using the American College of Obstetricians and Gynecologists database. We compared physician demographics, practice characteristics, and CD incision type preference.Results After exclusion of ineligible participants, 247 OB/GYNs completed the survey (42% response rate). In nonemergency CD of morbidly obese women, 84% of physicians preferred a Pfannenstiel skin incision (67% preferring taping the pannus; 17% without taping the pannus). In emergency CD, 66% preferred a Pfannenstiel incision (46% without taping the pannus; 20% with taping the pannus) and 20% a vertical incision. For both emergency and nonemergency CD, there was no difference in incision type preferences by provider years in practice, practice scope, or number of CD performed each year.Conclusion Given the preference of a Pfannenstiel incision with taping the pannus during CD of morbidly obese women, further investigation is needed to assess the risks and benefits of this incision and the practice of elevating the pannus.
Keywords: morbid obesity; postcesarean section; postoperative complication